1991
DOI: 10.1364/ao.30.001447
|View full text |Cite
|
Sign up to set email alerts
|

Frequency stabilization of a He–Ne laser using lateral stress

Abstract: Frequency stabilization of an internal mirror He-Ne laser by a new simple method is reported. In this method, the laser cavity length is modulated by stretching the front part of the laser tube using lateral stress; in this way the laser cavity length is stabilized on the Lamb dip. The relative frequency stability is +/-4.1 x 10(-9) over 1 h or longer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…7͒ is wrapped directly around the laser tube. Such heaters have been used by a number of authors for the same purpose, [8][9][10] and more exotic means of temperature control have been used as well. 2,11, 12 We note in passing that we experimented with Peltier coolers, and found that they were much more difficult to control in a stable manner.…”
Section: B Control Of Sealed-cavity Tubesmentioning
confidence: 99%
“…7͒ is wrapped directly around the laser tube. Such heaters have been used by a number of authors for the same purpose, [8][9][10] and more exotic means of temperature control have been used as well. 2,11, 12 We note in passing that we experimented with Peltier coolers, and found that they were much more difficult to control in a stable manner.…”
Section: B Control Of Sealed-cavity Tubesmentioning
confidence: 99%